(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Brain Computer Interface-spellers allow people with physical disabilities to communicate. The implementation of the full development of people with serious, purely physical disabilities and of the principles of equality and social justice require, in the current legal system, to promote such weak subjects considering legally relevant the will expressed through BCI-speller, suitable to allow the direct exercise of legal situations, first of all the right to self-determination with reference to non-patrimonial legal transactions. For post-human man the “custody” of the human is needed.